Late Quaternary faulting and paleoearthquakes along the northern section of the Bayanhaote fault and their implications for regional seismotectonics - Chen, Guihua; Li, Zhongwu; Huang, Xiongnan (Frontiers in Earth Science, 2022)
Analysis of the late Quaternary activity and paleo-seismicity of the Bayanhaote fault is critical because it is part of the frontier of the propagating Tibetan Plateau and the boundary between the Alxa and Ordos blocks, and the development of a regional seismotectonic model surrounding the Helan Mountains is crucial. We studied offset landforms and paleoearthquakes along the northern section of the Bayanhaote fault and found that it deformed dextrally, with a slight reverse slip to the east. A channel on the alluvial terrace, aged between 56.28 ± 4.04 ka and 82.2 ± 5.78 ka, is right-laterally offset by 137 m, and a sag pond formed on the east side of the fault scarp. We calculated a dextral slip rate of 1.67–2.43 mm/a. Three surface-rupturing paleoearthquakes were discovered in reversely offset strata in a trench south of Sumutu village. We infer that these three earthquakes might be a portion of surface-rupturing earthquakes by comparing them with documented paleoearthquake data along the southern half of the Bayanhaote fault. We established a regional seismotectonic model around the Helan Mountains using our new and published geological and geophysical data. The seismic risk along the dextral Bayanhaote fault to the west of the Helan Mountains is also substantial. The dextral Bayanhaote fault west of the Helan Mountains and the normal fault system in the east constitute the active boundary belt between the Alxa and Ordos blocks.